The Association Between Dietary Inflammatory Index and Cognitive Performance in Older Adults Aged 60 Years and Older - Song, Wenlei; Feng, Yijun; Gong, Zonglin; Tian, Changwei (Frontiers in Nutrition, 2022)
Background Neuroinflammation has been linked to the development of cognitive performance. Epidemiological evidence on dietary inflammatory potential and cognitive performance is scarce. We evaluated the association between dietary inflammatory index (DII) and cognitive performance in older adults. Methods This study included adults aged 60 years or older from the 2011–2014 National Health and Nutrition Examination Survey. The DII scores were calculated based on 27 nutritional parameters. Cognitive performance was assessed with four cognitive tests: the Digit Symbol Substitution Test (DSST, n = 2,780), the Consortium to Establish a Registry for Alzheimer’s Disease Word Learning (CERAD-WL, n = 2,859) and Delayed Recall (CERAD-DR, n = 2,857), and the Animal Fluency (AF, n = 2,844) tests. Restricted cubic splines and logistic regression were adopted to assess the associations. Results Comparing the highest to lowest tertile of DII scores, the odds ratio (95% CI) of lower cognitive functioning was 1.97 (1.08–3.58) [P-trend = 0.02, per 1 unit increment: 1.17 (1.01–1.38)] on DSST, 1.24 (0.87–1.76) [P-trend = 0.24, per 1 unit increment: 1.09 (0.96–1.23)] on CERAD-WL, 0.93 (0.57–1.51) [P-trend = 0.74, per 1 unit increment: 1.02 (0.87–1.20)] on CERAD-DR, and 1.76 (1.30–2.37) [P-trend < 0.01, per 1 unit increment: 1.17 (1.05–1.29)] on AF. The above-mentioned associations were observed in both men and women. In non-linear dose–response analysis, the association between DII and lower cognitive functioning was not significant at lower DII scores up to 3.0, after which the association was significant and the curve rose steeply. Conclusion Higher DII is associated with lower scores on DSST and AF tests in older adults.